Speeds of Decay of Temperature Distribution in a Laterally Insulated Copper Bar - Pokhrel, Puskar R. (Humanities and Social Sciences Journal, 2023)
Employing one-dimensional heat equation, speeds of decay of the temperature distribution in a laterally insulated copper bar are analyzed. Eigenfunctions and their corresponding Eigenvalues of the model equation are derived and analyzed with different period of time. The temperature distribution with given initial temperatures on copper bar in period of time are also analyzed. One-dimensional heat equation of a laterally insulated copper bar is also solved for examining and analyzing its temperature distribution Eigenfunction and corresponding Eigenvalues. Further, finite difference method is used to solve the temperature distribution numerically, and comparing its results with analytical solution.